2012
DOI: 10.1097/brs.0b013e31824ee8f7
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS Prize Winner

Abstract: Study Design NF-κB activity was pharmacologically and genetically blocked in an accelerated aging mouse model to mitigate age-related disc degenerative changes. Objective To study the mediatory role of NF-κB signaling pathway in age-dependent intervertebral disc degeneration. Summary of Background Data Aging is a major contributor to intervertebral disc degeneration (IDD), but the molecular mechanism behind this process is poorly understood. NF-κB is a family of transcription factors which play a central r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 44 publications
1
22
1
1
Order By: Relevance
“…Activation of RelA has been proposed to lead the systemic aging process in mice ( 86 , 87 ), being negligible in the hypothalamus of young mice and progressively increasing, earlier in microglia and later in neuronal cells, as the mice become older ( 12 ). The genetic depletion of one allele of RelA attenuated the behavioral signs of neurodegeneration and extended the healthspan in a progeroid mouse model ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of RelA has been proposed to lead the systemic aging process in mice ( 86 , 87 ), being negligible in the hypothalamus of young mice and progressively increasing, earlier in microglia and later in neuronal cells, as the mice become older ( 12 ). The genetic depletion of one allele of RelA attenuated the behavioral signs of neurodegeneration and extended the healthspan in a progeroid mouse model ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB signalling pathway is significantly correlated with the process of IDD. Inhibiting the activation of NF-κB can significantly retard the degree of disc degeneration [13, 28]. It was also reported that the SDF-1/CXCR4 axis induces apoptosis of human degenerative NPCs via the NF-κB pathway [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that GDF-5 was essential for the normal lamellar architecture of the AF and the structure of the NP (Li et al ., 2004), and that a deletion of type IX collagen led to premature onset of IVD degeneration (Boyd et al ., 2008). Recently, the DNA repair deficient mouse model of accelerated aging, which had been reported to exhibit age-related IVD degeneration, was used to explore the role of the NFκB signalling pathway in the onset of age-dependent degenerative changes (Nasto et al ., 2012). …”
Section: Preclinical Modelsmentioning
confidence: 99%